Effect of Different Concentration of Salinity on the Survival and Feeding of fingerling, Silver Carp (Hypophthalmichthys molitrix) (Valenciennes, 1844) - Abdullah, S.A.G. (Mesopotamian Journal of Marine Sciences, 2022)
In the present study, different concentration of salinity (4, 6, 8, 12 and 14 ppt) was studied for 21 days during December 2015, and compared with 1.4 ppt to investigate its effects on growth, nutrition and survival percentage rate of Silver carp (Hypophthalmichthys molitrix). The average of water temperature was 18.17 °C±1.3, dissolved oxygen was 7.9±0.60 (mg/l), hydrogen ion (8.13±0.327). The study showed that the mortality percentage for fish exposed to 14 ppt of salinity was 100 % after 24 hours, while the others was exposed to different concentration of salinity (4, 6, 8 and 12 ppt) were 0, 0, 0 and 25 % respectively after 21 days comparing with control (1.4 ppt) was 0 %. Inversely relationship was seen between food intake percentage and various concentration of salinity, the highest percentage of food intake 6.11 % in treatment of control (1.4 ppt) and the lowest 1.99 % in concentration 12 ppt. Statistic analysis was demonstrated that there significant differences (P<0.05) in rate of food intake ratio between treatments 1.4, 4, 6, 8 and 12 ppt.